ANALISIS FAKTOR PRIORITAS PENGEMBANGAN KOMODITAS PERKEBUNAN UNGGULAN DENGAN METODE AHP (ANALTYCAL HIERARCHY PROCESS - Herdhiansyah, Dhian; Sudarmi, Sudarmi; Sakir, Sakir; Asriani, Asriani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
This study aims to determine the priority factors in the development of plantation commodities, including cocoa, coffee, coconut, and oil palm as substitutes in East Kolaka District-Southeast Sulawesi.The method used is the analytic hierarchy process (AHP) of expert choice software 11. The AHP method includes: (a) developing a hierarchy; (b) determining priorities, and (c) calculating the consistency ratio (CR). The consistency ratio test (CR) of Expert Choice 11software on priority factors in the development of leading plantation commodities was obtained from each resource person (informant) from: (a) the Department of Agriculture; (b) Plantation Service; (c) Trade, Industry, Small and Medium Enterprises Office; (d) traders; (e) Gapoktan; (f) banking, and (g) academics. The study shows acceptable or consistent results because of CR<0.100. AHP analysis indicates that the priority factors for developing superior plantation commodities in East Kolaka Regency include: (a) feasible for business development (LBPB) 26.7%; (b) contribution of community income (KPM) 18.0%; (c) Added value (NT) 13.3%; (d) local government policies (KPD) 11.0%; (e) land suitability (KL) 10.5%; (f) market orientation (OP) 10.7%; and (g) non-conformance with environmentally friendly standards (RL) 9.7%. Keywords: analytical hierarchy process (AHP), expert choice 11, superior plantation commodities